Multidisciplinary Work Practices: A Comparison of Three Major European Hospitals - Kane, Bridget (IEEE, 2014)
This paper reviews the practices of multidisciplinary teamwork (MDT) for cancer care in three large teaching hospitals in separate jurisdictions. Ethnographic observations provide the main source of data, which are verified though interviews, and in some cases by surveys and analysis of video recordings. We demonstrate how MDT practices develop among different groups, and in different jurisdictions. Common practices are identified and differences explained. Work practice analysis is an integral part of our research, and this study provides insights into medical teamwork and decision-making.
27th International Symposium on Computer Based Medical Systems
PUBLISHED
New York, USA
Keywords: Cancer; Health Services Delivery; Health service management